Science fiction – złudzenie czy proroctwo przyszłości ? - Lisek, Marcin (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2008)
Science fiction is considered to be something worse, trivial entertainment for the unsophisticated. Is that right? The world around us is filled with numerous technical gadgets; if we take a closer look at them and compare them to the inventions present in science fiction we will discover frequently surprising futurological nature of this branch of literature. Science fiction is inspirational for scientists as it shows them potential developmental paths of the existing technologies, but it also predicts the birth of utterly new sciences. The questions posed by science fiction authors also concern the future society and the condition of the human being. This science fiction becomes a prophecy of tomorrow, showing us what future threats we may encounter as a result of improper application of the technologies of today.
Science Fiction - A Delusion or Prophecy ?